2020
DOI: 10.1504/ijims.2020.110256
|View full text |Cite
|
Sign up to set email alerts
|

The development of knowledge-shelf to enable an effective set-based concurrent engineering application

Abstract: This paper presents the development of knowledge-shelf (K-shelf) concept to enable set-based concurrent engineering (SBCE) application via knowledge provision. Three main outcomes are presented: 1) concept of the K-shelf in supporting designers throughout SBCE process; 2) demonstrates the concept via web-based software; 3) an industrial case study of surface jet pump (SJP) is also presented to validate the K-shelf concept and its software demonstrator. The K-shelf capabilities of capturing and storing design r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Obtained information from the literature showed that ToCs could be used in the highlighted activities of the SBCE process model as illustrated in Figure 2. Suwanda et al (2020) develop a software demonstrator of knowledge-shelf that captures design rationale in a structured manner to enable effective application of SBCE where ToC is used to visualise knowledge and narrowing down the design set.…”
Section: Minimum Uncertaintymentioning
confidence: 99%
“…Obtained information from the literature showed that ToCs could be used in the highlighted activities of the SBCE process model as illustrated in Figure 2. Suwanda et al (2020) develop a software demonstrator of knowledge-shelf that captures design rationale in a structured manner to enable effective application of SBCE where ToC is used to visualise knowledge and narrowing down the design set.…”
Section: Minimum Uncertaintymentioning
confidence: 99%
“…Some design studies introduced it to companies with positive results (Raudberget, 2010; Al-Ashaab et al , 2013; Miranda De Souza and Borsato, 2016; Schulze, 2016; Maulana et al , 2017), with participants going as far as to state it should be used at most times (Raudberget, 2010). Other studies use SBCE and related methods in computational assistants (Wang and Terpenny, 2003; Nahm and Ishikawa, 2004; Canbaz et al , 2013; Dafflon et al , 2017) or create tools to facilitate the process itself (Raudberget, 2011; Miranda De Souza and Borsato, 2016; Suwanda et al , 2020); however, these tools have not been applied to study the impacts of SBCE. Additionally, industry exposure to SBCE as described is still primarily through academic study, indicating that it is still in a research phase (Lycke, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The farmers must pay close attention to fruit ripeness conditions throughout the dates harvest season in September of every year and begin harvesting at the appropriate stage. Currently, the entire harvest process is manual, which means every date on X Ishikawa and Sasaki, 2020 [13] X X Small et al, 2020 [14] X X Suwanda, Al-Ashaab and Beg, 2020 [15] X Ammar et al, 2019 [16] X X X Fitzgerald and Ross, 2019 [17] X X X Inoue and Suzuki, 2019 [18] X X Lopes and Zancul, 2019 [19] X Geoffroy et al, 2019 [20] X Schjøtt-Pedersen et al, 2019 [21] X Rempling et al, 2019 [22] X X Saad et al, 2019 [23] X X Wade et al, 2019 [24] X X Rapp et al, 2018 [25] X Riaz et al, 2017 [26] X X Landahl et al, 2016 [27] X X X Miranda De Souza and Borsato, 2016 [28] X Levandowski, Müller and Isaksson, 2016 [29] X Araci, Al-Ashaab and Maksimovic, 2016 [30] X X Al-Ashaab et al, 2016 [31] X X Raudberget, Michaelis and Johannesson, 2014 [32] X X X…”
Section: Introductionmentioning
confidence: 99%
“…3) Supporting SBCE: Articles in this category suggest tools and techniques to assist SBCE applications rather than directly implementing SBD (e.g., developing knowledge while exploring the design space [10]). 4) SBCE as an approach: Set-based design is not solely used, rather it is used in conjunction with other approaches to product development.…”
Section: Introductionmentioning
confidence: 99%